MERITOKRASI DALAM PROMOSI JABATAN PADA SEKRETARIAT DAERAH KABUPATEN MERAUKE - Sil Maria Ungirwalu; Suratma suratman (Universitas Musamus, Merauke, Papua, 2012)
Meritocracy is an effort to improve the performance of employees in order to achieve the productivity of a bureaucratic institution or high. This research aims to find out how the meritocracy in the Promotion Office of the Secretariat of the Merauke Area. The research method used is descriptive qualitative techniques with a focus on career development in structural terms must be met civil servants as well as education and training must be followed by every civil servant. The results showed that the career development officer at the Secretariat of the Merauke Area pretty well seen from the employee recruitment system for the formation of the Office of Echelon always refer to the competence of employees. Education and training of employees of the Secretariat of The Merauke is also quite good views of how employees can complete their work on time.It was concluded that the meritocracy in the development promotion Office at the Secretariat of the Merauke Region was well underway and is expected to be fixed in order to increase the performance of the bureaucracy